MENGAPRESIASI SASTRA GENRE PUISI MELALUI KEGIATAN PARAFRASE PADA LIRIK LAGU âSAKITNYA TUH DI SINIâ - Kurniati, Lisdwiana (JURNAL PESONA, 2015)
AbstractÂ There are several ways to appreciate literature, especially poetry genre besides activities to understand the fundamental and elements contained in the literature. One of them is paraphrasing the song lyrics. Paraphrases activities were taught in schools ranging from Elementary, Junior High, Senior High and Universities. The results of this study can be used as the concrete illustration or creative and innovative literature learning alternative ways in literature appreciating activity. Paraphrase activity of poetry genre can be done through bound paraphrasing and free paraphrasing. This study uses qualitative descriptive method by analyzing the data and presenting it straightly. The result shows that the song lyric of âsakitnya tuh di siniâ contains of disappointment because of infidelity lover or disappointed of betrayed love.Â Key Words: Literature, Paraphrase, Song Lyric.Â